2023
DOI: 10.61650/dpjpm.v1i1.199
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Differentiated Learning on Improving Student Learning Outcomes

Aguanda,
Agus Setiawan,
M. Saidun Anwar
et al.

Abstract: This research aims to obtain objective information and examine differences in the abilities of reasoning mathematical students who study with method learning differentiate assistance with RME-based matrix teaching materials from students who use conventional methods. This research uses a quantitative approach with experimental research methods pseudo (quasi-experiment) with type non-equivalent control groups design. The study was carried out in the even semester of the 2022/2023 academic year in the mathematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The study's results demonstrated the effectiveness of DLE in creating a classroom environment that facilitates better comprehension of the material (Dinç, 2017). Another study by Aguanda et al revealed that differentiated learning, supported by matrix-based RME teaching materials, can improve the mathematical reasoning abilities of 11th-grade APHP students at SMK Negeri 2 Metro Lampung (Aguanda et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…The study's results demonstrated the effectiveness of DLE in creating a classroom environment that facilitates better comprehension of the material (Dinç, 2017). Another study by Aguanda et al revealed that differentiated learning, supported by matrix-based RME teaching materials, can improve the mathematical reasoning abilities of 11th-grade APHP students at SMK Negeri 2 Metro Lampung (Aguanda et al, 2023).…”
Section: Resultsmentioning
confidence: 99%